The Role of Sphingolipids in the Pathogenesis of Psoriasis - Mateusz Matwiejuk; Hanna Mysliwiec; Adrian Chabowski; Iwona Flisiak (Metabolites, 2022)
Psoriasis is a complex, chronic, immunologically mediated disease which involves skin and joints. Psoriasis is commonly connected with numerous other diseases such as liver diseases, metabolic syndrome, impaired glucose tolerance, diabetes mellitus, atherosclerosis, hypertension, and ischemic heart disease. Interestingly, comorbidities of psoriasis are an attention-grabbing issue. Additionally, it can cause impairment of quality of life and may be associated with depressive disorders. Altered levels of ceramides in psoriatic skin may lead to anti-apoptotic and pro-proliferative states, consequently leading to an over-proliferation of keratinocytes and the development of skin lesions. The pathophysiology of psoriasis and its comorbidities is not fully understood yet. Sphingolipids (including ceramides) and their disturbed metabolism may be the link between psoriasis and its comorbidities. Overall, the goal of this review was to discuss the role of sphingolipid disturbances in psoriasis and its comorbidities. We searched the PubMed database for relevant articles published before the beginning of May 2022. The systematic review included 65 eligible original articles.